VLSI and Post-CMOS Electronics. Volume 2 : Devices, circuits and interconnects - Dhiman, Rohit; Chandel, Rajeevan (Materials, circuits and devices series ;, 2019)
The following topics are dealt with: integrated circuit design; VLSI; technology CAD (electronics); MOSFET; III-V semiconductors; silicon; semiconductor device models; SRAM chips; three-dimensional integrated circuits; permittivity.